Peningkatan Hasil Belajar Siswa Mata Pelajaran PAI Materi Menyambut Usia Baligh Melalui Media Diskusi Dan Media Audio Visual Kelas IV SD N 10 Simpang Selatan Kecamatan Simpang Alahan Mati Kabupaten Pasaman - Jafril, Jafril (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students' learning outcomes in Islamic Religious Education on the topic "Welcoming Puberty" through the use of discussion and audio-visual media. This classroom action research was conducted in two cycles involving 10 fourth-grade students at SD Negeri 10 Simpang Selatan. In Cycle I, the use of discussion and audio-visual media enhanced students' understanding of the material but did not achieve 100% mastery learning. Through improvements in Cycle II, all students achieved mastery learning with high scores in understanding, discussion participation, and presentation skills. The study results indicate that discussion and audio-visual media are effective in improving students' learning outcomes while supporting active and participatory learning. This strategy can be widely applied as an innovative approach in experiential-based learning.